2021
DOI: 10.1101/2021.03.01.433461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scaling of subcellular structures with cell length through decelerated growth

Abstract: How cells tune the size of their subcellular parts to scale with cell size is a fundamental question in cell biology. Until now, most studies on the size control of organelles and other subcellular structures have focused on scaling relationships with cell volume, which can be explained by limiting pool mechanisms. Here, we uncover a distinct scaling relationship with cell length rather than volume, revealed by mathematical modeling and quantitative imaging of yeast actin cables. The extension rate of cables d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Another possible use for such a gradient could be in controlling the self-assembly of linear structures such as actin cables and flagella, which are precisely scaled to the linear dimensions of the cell [29], [30], [31]. For example, a recent study of actin cables in yeast found that when cells were mutated to grow abnormally large, the actin cables assembled to a length that was proportional to the cell radius [32]. A hypothesized explanation of this phenomena is the presence of a scale-invariant gradient of depolymerizing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible use for such a gradient could be in controlling the self-assembly of linear structures such as actin cables and flagella, which are precisely scaled to the linear dimensions of the cell [29], [30], [31]. For example, a recent study of actin cables in yeast found that when cells were mutated to grow abnormally large, the actin cables assembled to a length that was proportional to the cell radius [32]. A hypothesized explanation of this phenomena is the presence of a scale-invariant gradient of depolymerizing activity.…”
Section: Discussionmentioning
confidence: 99%